Revue de Nora Berend, Stephen I, the First Christian King of Hungary - de Cevins, Marie-Madeleine (Acta Mediaevalia. Series Nova, 2024)
Review of the following book (in French) : Stephen I,the First Christian King of Hungary. From Medieval Myth to Modern Legend, Oxford, Oxford University Press, 2024, 272 p.